Niektóre problemy związane z opozycją polityczną - Machelski, Zbigniew (Polityka i Społeczeństwo, 2020)
The opposition is an institution of the political regime, whose essential function is to allow alternation of power. According to the political scientist, it is a phenomenon from the sphere of governance, where different imperious and subordinate entities are in a relationship with partially common goals and partly contradictory, but remain always mutually dependent. The importance of the political opposition depends not only on the adopted institutional solutions, but primarily the political culture. Just as every society has the government it deserves, by analogy, the same is also true of the opposition.